DNA barcoding of Crustacean larvae in the eastern areas of Segara Anakan Cilacap, Central Java Indonesia - KUSBIYANTO KUSBIYANTO; DIAN BHAGAWATI; Agus Nuryanto (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kusbiyanto, Bhagawati D, Nuryanto A. 2020. DNA barcoding of crustacean larvae in Segara Anakan, Cilacap, Central Java, Indonesia using cytochrome c oxidase gene. Biodiversitas 21: 4878-4887. Species-level identification of crustacean larvae is challenging due to morphological constraints. DNA barcoding offers a precise method to solve the problems. That method has never been applied to crustacean larvae from the eastern of Segara Anakan, Cilacap, Central Java, Indonesia. This study aims to identify crustacean larvae in the eastern of Segara Anakan using the cytochrome c oxidase subunit I (COI) gene as a barcode marker. Larvae morphotypes were identified under a binocular microscope. The COI gene was sequenced from one individual of each morphotype. Microscopic observation placed the samples into 15 morphotypes. DNA barcoding placed twelve morphotypes as Crustacea with sequence homologies from 72.21% to 99.21%. Intra-species genetic divergences between samples and reference species ranged between 0.9% and 31.9%, while genetic distance ranged from 0.0% to 17.80%. Intra-species genetic divergences ranged between 0.00% and 3.9%, while genetic distance ranged from 0.00% to 3.8%. The phylogenetic tree proved the monophyly between samples and reference species and showed clear separation among species. All parameters proved that nine morphotypes were identified into species level and were counted for five species. Three morphotypes were identified into the genus level and were counted for three genera. Eight species of crustacean larvae were successfully identified using the cytochrome c oxidase subunit 1 gene.